Pemetaan Kemampuan Berbicara Bahasa Korea Para Instruktur LPK Bahasa Korea melalui Pra-Penilaian dengan Rekaman Audio - Rosyadi, Alfiana Amrin; Laksita, Ersta Bunga (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
A continuous training of trainers (ToT) of Korean language who teach in Training Institutions has been conducted by Korean Language and Culture Program Studies since 2019. This training was a cooperation with the Association of Korean Language Training Institutions or well known as PELBAKORI. In the past training, Korean language ability mapping using pre-assessment of trainers has not been done. Therefore, Korean speaking ability mapping was conducted by examining the pronunciations and skill of understanding and answering of questions. To collect data, we used the recording, and those recordings that were sent before the training program were analyzed and classified into each type of error. In the future, this collected data can be a reference for designing books for trainers and also be data for future research related to Korean Language Trainers. === Pelatihan kepada para instruktur bahasa Korea di lembaga pelatihan kerja (LPK) diadakan secara berkelanjutan oleh Prodi Bahasa dan Kebudayaan Korea, Universitas Gadjah Mada bekerja sama dengan Perkumpulan Lembaga Pelatihan Bahasa Korea di Indonesia (PELBAKORI). Di pelatihan-pelatihan sebelumnya, pemetaan kemampuan peserta pelatihan tidak dilakukan sehingga prodi tidak tahu sejauh mana kemampuan bahasa Korea para instruktur. Oleh karena itu, pemetaan kemampuan berbicara dilakukan dengan cara menguji pelafalan dan kemampuan memahami dan menjawab pertanyaan. Untuk mengumpulkan data tersebut, peserta pelatihan diminta mengirimkan rekaman. Rekaman kemudian dianalisis untuk menjadi bahan acuan tim dalam melaksanakan pelatihan. Ke depan, data ini bisa jadi data untuk pengembangan buku atau penelitian tentang kemampuan bahasa Korea instruktur.